2020
DOI: 10.2172/1659816
|View full text |Cite
|
Sign up to set email alerts
|

Least-Cost Pathways for India's Electric Power Sector

Abstract: Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 2 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…Hourly electricity and hydrogen balance as well as reserve constraints are incorporated for each region. Flexibility constraints for thermal units are also included with maximum and minimum generation limits defined, and with specification of ramping and minimum on/off time constraints shown in Table S11 with data referenced from previous studies (Lu et al, 2020;Ministry of Power, 2019;Palchak et al, 2017;Rose et al, 2020;Sharma et al, 2018;Sinha, 2020). Operational constraints relating to energy storage are also considered based on different characteristics of storage technologies.…”
Section: Hydrogen Technology Optionsmentioning
confidence: 99%
“…Hourly electricity and hydrogen balance as well as reserve constraints are incorporated for each region. Flexibility constraints for thermal units are also included with maximum and minimum generation limits defined, and with specification of ramping and minimum on/off time constraints shown in Table S11 with data referenced from previous studies (Lu et al, 2020;Ministry of Power, 2019;Palchak et al, 2017;Rose et al, 2020;Sharma et al, 2018;Sinha, 2020). Operational constraints relating to energy storage are also considered based on different characteristics of storage technologies.…”
Section: Hydrogen Technology Optionsmentioning
confidence: 99%
“…More information about ReEDS can be found in Ho et al (2021), and details on its application to India can be found in Rose et al (2020). The model is implemented in the General Algebraic Modeling System (GAMS) programming language.…”
Section: Modeling Frameworkmentioning
confidence: 99%
“…Additional work on cross-border electricity trade in the region helped clarify how India's renewable energy ambitions would impact regional opportunities (McBennett et al 2019;Joshi, Hurlbut, and Palchak 2020). And several studies of the next phase of policy targets for 2030 have shed light on what additional planning and operational challenges may be faced in the coming years (CEA 2018;Abhyankar, Deorah, and Phadke 2021;Rose et al 2020;Chernyakhovskiy et al 2021).…”
Section: High Renewable Energy Grids Are Required For Decarbonizationmentioning
confidence: 99%